Daya Hambat Ekstrak Non-Polar (n-Heksan) Daun Ladhangka (Lunasia amara Blanco) Terhadap Bakteri Escherichia coli - Nurwahidah Nurwahidah; Rustam Musta; Abraham Rahman (Science and Education Journal (SICEDU), 2026)
A study has been conducted on the inhibitory effect of non-polar (n-hexane) extract of Ladhangka leaves (Lunasia amara Blanco) against Escherichia coli bacteria. The purpose of this study is to find out the compounds contained in the non-polar (n-hexane) extract of Ladhangka leaves obtained through the extraction process and to determine the inhibitory effect of the n-hexane extract of Ladhangka leaves on the growth of Escherichia coli bacteria. The extraction was done using the maceration method with n-hexane as the solvent, followed by phytochemical screening, identification using Thin Layer Chromatography (TLC), compound analysis with Gas Chromatography-Mass Spectrometry (GC-MS), and antibacterial activity tests using the disc diffusion method at concentrations of 75%, 50%, 25%, and 12.5% during 24 and 48 hours of incubation. GC-MS analysis results identified 4 main compound components, namely 2-Propenyl, 2-propenoate, 5-cyclopropylidene-, 1-pentanol, 2,3,5-trimethyl-4-methylene-2-cyclopenten-1-one, and Methyl-ω-3 Arachidonate. However, antibacterial activity tests showed that the n-hexane leaf extract of Lunasia amara Blanco at all tested concentrations (75%, 50%, 25%, and 12.5%) was unable to inhibit the growth of Escherichia coli bacteria, as indicated by the absence of an inhibition zone (0 mm).